Effect of a VITAFERT microbial additive on some bioproductive and health indicators in growing pigs - Ruiz Quintana, David; Lazo Pérez, Leonel (My University, 2017)
In order to evaluate the effect of VITAFERT on some bioproductive and health indicators of growing pigs under production conditions, two groups of animals of 240 pigs each were used. Group A represented the control, and B was supplied with 10 mL of VITAFERT/kg of live weight as a supplement in the feed. The food intake, the increase, the average daily gain, food conversion and viability were determined, as well as the occurrence of diarrheal episodes by recording the epizootic indexes of morbidity, mortality and lethality, associated with diarrheal processes. The relative risk was also estimated through the conformation of 2 x 2 contingency tables, applying an observational analytical study of cohort type and an economic valuation of the application of the product was carried out. It is concluded that the pigs supplemented with VITAFERT improve the bioproductive indicators of live weight increase, average daily gain, feed conversion and viability. They also show lower rates of morbidity, mortality and lethality before diarrhea. The risk of death in pigs that did not intake VITAFERT was higher than in those supplemented with this product and death losses were higher in pigs that did not intake VITAFERT.

Para evaluar el efecto del VITAFERT en algunos indicadores bioproductivos y de salud de cerdos en crecimiento en condiciones de producción, se utilizaron dos grupos de animales, de 240 cerdos cada uno. El grupo A representó el control, y al B se le suministró 10 mL de VITAFERT/kg de peso vivo como suplemento en el pienso. Se determinó el consumo de alimento, el incremento, la ganancia media diaria, conversión alimentaria y viabilidad, así como la ocurrencia de episodios diarreicos mediante el registro de los índices epizoóticos de morbilidad, mortalidad y letalidad, asociados a procesos diarreicos. Se estimó además, el riesgo relativo mediante la conformación de tablas de contingencia 2 x 2, aplicándose un estudio analítico observacional de tipo cohorte y se realizó una valoración económica de la aplicación del producto. Se concluye que los cerdos suplementados con VITAFERT mejoran los indicadores bioproductivos de incremento de peso vivo, ganancia media diaria, conversión alimentaria y viabilidad. Manifiestan además, menores índices de morbilidad, mortalidad y letalidad ante diarreas. El riesgo de muerte en los cerdos que no consumieron VITAFERT fue mayor que en los suplementados con este producto y las pérdidas por concepto de muerte fueron mayores en los cerdos que no consumieron VITAFERT.
Efecto de un aditivo microbiano VITAFERT en algunos indicadores bioproductivos y de salud en cerdos en crecimiento
Keywords: VITAFERT; Probiotics; Diarrhea; Microbial Additive; Probióticos; Diarrea; Aditivo Microbiano